TOURIST PERCEPTIONS, BELIEFS, AND EVALUATIONS OF THE ARCTIC: A CASE STUDY OF THE MURMANSK REGION - Alyona S. Davydova (Север и рынок: формирование экономического порядка)
The Murmansk Region, located on the Kola Peninsula in the Arctic, is actively developing as a tourist destination. However, many aspects related to the marketing and representation of its cultural and natural heritage remain underexplored. The purpose of this article is to examine the image of the Murmansk Region as perceived through tourists’ beliefs, opinions, and evaluations of Arctic-specific attributes — factors that can play a decisive role in destination choice. The study is based on data from a sociological survey conducted in the city of Kirovsk, one of the region’s major tourist hubs.